2007
DOI: 10.1002/prs.10194
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting of a silane explosion in a photovoltaic fabrication plant

Abstract: A second possible cause of a previously described silane explosion is proposed based on a more detailed examination of the physical evidence. The explosion and fire occurred in a silane gas room in a photovoltaic fabrication plant. This investigation recommends more research to investigate the characteristics of a silane release and the resulting fires and explosions. Suggestions are also made for a better silane cylinder valve design and cabinet design. Silane leaks are difficult to detect; therefore the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…In a semi-confined space with gas accumulation, the pop can lead to a gas explosion with significant damage (Ngai et al, 2007). Chang et al (2007) and Chen et al (2006) have reported a destructive silane explosion that is caused by the release and delayed ignition and explosion from a silane cylinder. The incident stressed the importance of understanding the mechanism of delayed ignition from silane release.…”
Section: Introductionmentioning
confidence: 99%
“…In a semi-confined space with gas accumulation, the pop can lead to a gas explosion with significant damage (Ngai et al, 2007). Chang et al (2007) and Chen et al (2006) have reported a destructive silane explosion that is caused by the release and delayed ignition and explosion from a silane cylinder. The incident stressed the importance of understanding the mechanism of delayed ignition from silane release.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2006), Chang et al (2007) and Peng et al (2008). The cause of leak is a failed silane cylinder valve with loosened valve stem retainer.…”
Section: Incidents and Emergency Response 41 Silanementioning
confidence: 98%
“…A TNT equivalency model using a yield factor of 1 and accounting for one reflecting surface was used to fit the overpressure data. Ngai et al (2007) performed release and explosion tests from cylinder and gas cabinet following the tragic silane explosion incident in 2005 (Chen et al, 2006;Chang et al, 2007). In these particular experiments, it was demonstrated that ignition was triggered by flow shutoff at the outlet rather than by autoignition of metastable silane/air mixture in the gas cloud.…”
Section: Introductionmentioning
confidence: 96%